2018
DOI: 10.1186/s13046-018-0876-2
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase 3-like 1-CD44 interaction promotes metastasis and epithelial-to-mesenchymal transition through β-catenin/Erk/Akt signaling in gastric cancer

Abstract: BackgroundEnzymatically inactive chitinase-like protein CHI3L1 drives inflammatory response and promotes tumor progression. However, its role in gastric cancer (GC) tumorigenesis and metastasis has not yet been fully elucidated. We determined the significance of CHI3L1 expression in patients with GC. We also explored an as-yet unknown receptor of CHI3L1 and investigated the involved signaling in GC metastasis.MethodsCHI3L1 expression was evaluated by immunoblotting, tissue microarray-based immunohistochemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
80
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 62 publications
1
80
1
2
Order By: Relevance
“…β-Catenin is one of the core proteins in the Wnt signaling pathway, and it was shown that phosphorylation at Ser552 and Ser675 of β-catenin could activate the β-catenin mediated signaling pathway. [24][25][26] In this study, in EYA4 overexpressed cells and EYA4 KO cells, the total level of β-catenin and p675-β-catenin did not change, but the level of p552-β-catenin was decreased in EYA4 overexpressed cells and increased in EYA4 KO cells. To investigate whether p552-β-catenin can facilitate transcription of MYCBP, we established β-catenin overexpressed plasmids with (WT) or without S552A mutation, a negative phosphorylated mutation of β-catenin at Ser552.…”
Section: Discussionmentioning
confidence: 49%
“…β-Catenin is one of the core proteins in the Wnt signaling pathway, and it was shown that phosphorylation at Ser552 and Ser675 of β-catenin could activate the β-catenin mediated signaling pathway. [24][25][26] In this study, in EYA4 overexpressed cells and EYA4 KO cells, the total level of β-catenin and p675-β-catenin did not change, but the level of p552-β-catenin was decreased in EYA4 overexpressed cells and increased in EYA4 KO cells. To investigate whether p552-β-catenin can facilitate transcription of MYCBP, we established β-catenin overexpressed plasmids with (WT) or without S552A mutation, a negative phosphorylated mutation of β-catenin at Ser552.…”
Section: Discussionmentioning
confidence: 49%
“…Further, adherens and tight junctions become impaired, resulting in a mesenchymal phenotype [12,[71][72][73]. Altered E-and N-cadherin levels and the following β-catenin activation promote the expression of many tumor-associated proteins, including cyclin D1, CD44, or c-MYC [54,[74][75][76][77][78][79]. A transformation of cell phenotype enhances the migratory properties,…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we examined CHI3L1 and NPTX2 protein levels and cellular expression in the FC, a region affected early by plaque pathology during the progression of AD. These proteins were compared with other glial neuroinflammatory markers such as microglial ionized calcium-binding adapter molecule 1 (Iba1), complement component 1q (C1q), TREM2, astrocytic glial fibrillary acidic protein (GFAP), and glial surface adhesion glycoprotein CD44, which interacts directly with CHI3L1 [47] and drives immune responses in the central nervous system [48]. These proteins were quantified using immunoblotting and immunohistochemistry or immunofluorescence techniques.…”
Section: Introductionmentioning
confidence: 99%